Carbon monoxide stunning of Atlantic salmon (Salmo salar L.) modifies rigor mortis and sensory traits as revealed by NIRS and other instruments. (29th December 2015) - Concollato, Anna; Parisi, Giuliana; Masoero, Giorgio; Romvàri, Robert; Olsen, Rolf‐Erik; Dalle Zotte, Antonella
Abstract: BACKGROUND: Methods of stunning used in salmon slaughter are still the subject of research. Fish quality can be influenced by pre‐, ante‐ and post‐mortem conditions, including handling before slaughter, slaughter methods and storage conditions. Carbon monoxide (CO) is known to improve colour stability in red muscle and to reduce microbial growth and lipid oxidation in live fish exposed to CO. Quality differences in Atlantic salmon, Salmo salar L., stunned by CO or percussion, were evaluated and compared by different techniques [near infrared reflectance spectroscopy (NIRS), electronic nose (EN), electronic tongue (ET)] and sensory analysis. RESULTS: Thawed samples, freeze‐dried preparates and NIRS devices proved to be the most efficient combinations for discriminating the treatments applied to salmon, i.e. first the stunning methods adopted, then the back‐prediction of the maximum time to reach rigor mortis and finally to correlate some sensory attributes. A trained panel found significant differences between control and CO‐stunned salmon: reduced tactile crumbliness, reduced odour and aroma intensities, and reduced tenderness of CO‐treated fillets. CO stunning reduced radiation absorbance in spectra of thawed and freeze‐dried fillets, but not fillet samples stored in ethanol, where it may have interacted with myoglobin and myosin. CONCLUSIONS: The good results in a rapid discrimination of thawed samples detected by NIRS suggest suitable applications in the fish industry. CO treatment could mitigate sensory perception, but consumer tests are needed to confirm our findings. © 2015 Society of Chemical Industry